Big data exchange based on information chain - Nan LIU; Jinwu WEI; Lu LIU (Dianxin kexue)
The flow and sharing of data is the foundation of the development of big data industry. However, facing with the specification of data itself and many problems that data trading modes have, the development of data flow and sharing moves slowly. Based on the block chain technology, a new decentralized data exchange platform was designed, which would secure the legal rights of data providers and realize the goal of safe circulation between the only mutual parties of the data exchange, strengthen the regulation and monitoring of flows data.